Histološka, anatomska in funkcijska organiziranost skorje osrednjega živčevja - Meh, Duška (Medicinski razgledi, 2000)
The cerebral cortex represents a relatively small part of the central nervous system. It contains a prodigious number of cells that lead our behaviour. In ageneral way, the central sulcus divides the cerebral cortex into a cerebral receptive portion and an anterior part related to motor function. Association areas interconnect cortical regions. Different cortices differ in arrangement,type and density of cortical cells, thus determining the individual.
Keywords: Cerebral cortex; osrednje živčevje; histologija; Anatomy and histology; Physiology; anatomija; Cerebellar cortex; fiziologija; Neurons